Expression patterns of fibroblast activation protein and extra-domain B fibronectin in canine malignant tumors - Dell’Aere, Silvia; Gariboldi, Elisa Maria; Ubiali, Alessandra; Ferrari, Roberta; Auletta, Luigi; Bocci, Matilde; Galbiati, Andrea; Gilardoni, Ettore; Rotta, Giulia; Balbi, Valentina; Bianchi, Gaia Beatrice Maria; Verdi, Alessandra; et al. (Frontiers in Veterinary Science, 2026)
IntroductionFibroblast activation protein (FAP) is involved in the extracellular matrix (ECM) remodeling and wound healing. Absent in most adult tissues, it is overexpressed by neoplastic cells and/or cancer-associated fibroblasts (CAFs) in several human malignancies. The extra Domain-B of fibronectin (EDB+FN) is a splice variant of fibronectin involved in angiogenesis and tissue remodeling, overexpressed by CAFs and cancer-associated vessels (CAVs) in many aggressive human tumors. This study aims to investigate FAP and EDB+FN expressions in canine tumors and assess their potential as druggable targets in animal patients.MethodsFAP and EDB+FN expression was assessed by immunohistochemistry on 88 canine tumors, including Soft Tissue Sarcomas [STS], Osteosarcomas [OSA], Hemangiosarcomas [HSA], Apocrine Gland Anal Sac Adenocarcinomas [AGASAC], Mast Cell Tumors [MCT], Lymphomas, and Melanomas, using polyclonal and monoclonal anti-FAP and the L19 anti-EDB antibodies. Expression distribution and intensity were semi-quantitatively scored in neoplastic cells, CAFs, CAVs, and stroma.ResultsFAP was variably expressed in neoplastic cells (79/88), CAFs (79/88), and CAVs (82/88) across all tumor types, but mostly in AGASACs, STSs, and MCTs. The monoclonal antibody presented greater specificity. EDB+FN expression was less present across tumor types, mostly with a vascular staining pattern. Labelling was most intense and consistent in the neoplastic cells, CAFs, and CAVs of melanomas, and to a lesser extent in AGASAC and STS.DiscussionSTS, AGASAC, and MCT could be candidates for FAP-targeted strategies; melanomas are the most promising for EDB+FN-directed therapies. These results support FAP and EDB+FN as targets worth investigating for clinical applications in animal patients.